2014
DOI: 10.1016/j.ijcard.2014.07.011
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of acupuncture in stable ischemic heart disease patients

Abstract: Background Heart rate variability (HRV) is reduced in stable ischemic heart disease (SIHD) patients and is associated with sudden cardiac death (SCD). We evaluated the impact of traditional acupuncture (TA) on cardiac autonomic function measured by HRV in SIHD patients. Methods We conducted a randomized controlled study of TA, sham acupuncture (SA), and waiting control (WC) in 151 SIHD subjects. TA group received needle insertion at acupuncture sites, SA group received a sham at non-acupuncture sites, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 67 publications
0
24
0
1
Order By: Relevance
“…We read the recent article titled "A randomized controlled trial of acupuncture in stable ischemic heart disease patients" written by Puja K. Mehta et al with interest [1]. I am focusing on the traditional medicine in the diagnosis and treatment in cardiovascular disease, especially coronary heart disease.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…We read the recent article titled "A randomized controlled trial of acupuncture in stable ischemic heart disease patients" written by Puja K. Mehta et al with interest [1]. I am focusing on the traditional medicine in the diagnosis and treatment in cardiovascular disease, especially coronary heart disease.…”
Section: Dear Editormentioning
confidence: 99%
“…Unfortunately, there were no group differences for such measures. In Puja K. Mehta's article, they thought that TA technique could significantly reduce angina pectoris in stable ischemic heart disease (SIHD) [1,2]. However, to the best of our knowledge, such secondary outcome measures cannot reflect the degree of myocardial ischemia, which is the physiopathologic mechanism of angina pectoris.…”
Section: Dear Editormentioning
confidence: 99%
“…One trial compared genuine and sham acupuncture and found no difference in improvement of angina frequency or severity of attacks between the two groups, although there was a median reduction of 50% in anginal attack rate in both groups, implying a potentially beneficial effect from both genuine and sham acupuncture treatments . A similar study conducted in patients with stable ischaemic heart disease found a significant increase in heart rate variability, which has positive prognostic value, in patients receiving genuine acupuncture compared with sham treatment . T'ai chi has also been evaluated as a potential therapy and, whilst it does not modify measures such as heart rate variability, it has been demonstrated to improve baroreflex sensitivity .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there were no group differences for such measures. In Puja K. Mehta's article, they thought that TA technique could significantly reduce angina pectoris in stable ischemic heart disease (SIHD) [1,2].…”
Section: Dear Editormentioning
confidence: 99%